Analysis of Factors Influencing to Hydroponic Purchasing Decision in Pangkalpinang: A Particial Least Squares Structural Equation Modelling (PLS-SEM) Approach - Dewa Ayu Gianina; Muhammad Yamin; Selly Oktarina (Journal of Social Research, 2024)
The rapid growth of urbanization and increased health awareness among consumers in Pangkalpinang City have led to a growing interest in hydroponic vegetables. This study aims to analyze the factors influencing consumer purchasing decisions for hydroponic vegetables in Pangkalpinang. Using a quantitative approach, data were collected from 170 respondents through surveys, focusing on economic social, psychological factors, and marketing stimuli. The research employed Particial Least Squares Structural Equation Modelling analysis to identify significant predictors of purchasing decisions. The direct effects analysis indicates that perception (p-value = 0.004), attitude (p-value = 0.001), product quality (p-value = 0.000), and income (p-value = 0.000) significantly influence purchasing decisions, while motivation (p-value = 0.464) and price (p-value = 0.644) do not have a significant effect. The indirect effects analysis shows that price influences purchasing decisions through perception (p-value = 0.000) but not through motivation (p-value = 0.567). Similarly, product quality impacts purchasing decisions through perception (p-value = 0.006), while its indirect effect through motivation is insignificant (p-value = 0.425). These findings suggest that product quality and consumer perception play crucial roles, while price exerts an indirect influence to purchasing decision. This research provides essential insights for hydroponic entrepreneurs, emphasizing the importance of enhancing product quality and consumer perception to improve market strategies.